Sarcopenic Obesity in Heart Failure With Preserved Ejection Fraction - Kirkman, Danielle L.; Bohmke, Natalie; Billingsley, Hayley E.; Carbone, Salvatore (Frontiers in Endocrinology, 2020)
Heart failure with preserved ejection fraction (HFpEF) is a public health epidemic that is projected to double over the next two decades. Despite the high prevalence of HFpEF, there are currently no FDA approved therapies for health-related outcomes in this clinical syndrome making it one the greatest unmet needs in cardiovascular medicine. Aging and obesity are hallmarks of HFpEF and therefore there is a high incidence of sarcopenic obesity (SO) associated with this syndrome. The presence of SO in HFpEF patients is noteworthy as it is associated with co-morbidities, worsened cardiovascular health, hospitalizations, quality of life and mortality. Furthermore, SO plays a central role in exercise intolerance, the most commonly reported clinical symptom of this condition. The aim of this review is to provide insights into the current knowledge pertaining to the contributing pathophysiological mechanisms and clinical outcomes associated with HFpEF-related SO. Current and prospective therapies to address SO in HFpEF, including lifestyle and pharmaceutical approaches, are discussed. The urgent need for future research aimed at better understanding the multifaceted physiological contributions to SO in HFpEF and implementing interventional strategies to specifically target SO is highlighted.